The Influence of Islamic Financial Literacy, Islamic Financial Inclusion, and Locus of Control on the Financial Performance of Muslim MSMEs in Pekanbaru City - Saputri, Sri Wulan; Ramashar, Wira; Rodiah, Siti (Islamic Business and Management Journal, 2025)
This study aims to analyze the influence of Islamic financial literacy, Islamic financial inclusion, and locus of control on the financial performance of Muslim MSMEs in Pekanbaru City. The research employs a quantitative approach using a survey method through questionnaires distributed to 100 Muslim MSME actors selected using convenience sampling. Data analysis was conducted using Structural Equation Modeling (SEM) based on SmartPLS 4.0. The results show that Islamic financial literacy has a significant positive effect on the financial performance of MSMEs. Likewise, Islamic financial inclusion has a significant positive effect on MSME financial performance. Furthermore, locus of control also has a significant positive effect on MSME financial performance. The coefficient of determination (R²) value of 0.274 indicates that these three variables explain 27.4% of the variation in the financial performance of MSMEs. These findings highlight the importance of increasing understanding of Islamic financial principles, improving access to Islamic financial services, and strengthening self-control and personal responsibility in managing business finances.